Organic-inorganic hybrid flame-retardant adhesive based on tannic acid and preparation method of organic-inorganic hybrid flame-retardant adhesive

The organic-inorganic hybrid flame retardant adhesive with tannin acid, hyperbranched polymer and surface modification of magnesium hydroxide nanoparticles is solved by solving the problems of formaldehyde release of traditional adhesives and the influence of mechanical properties, and the adhesive with high strength, water resistance and flame retardant properties is achieved for wood bonding and plywood.

CN120248822APending Publication Date: 2025-07-04SOUTHWEST FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510214729.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-19
Filing Date
2025-02-26
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

Existing adhesives have formaldehyde release problems, which are difficult to meet the needs of high-performance and environmentally friendly adhesives. The addition of traditional flame retardant will affect the mechanical properties of plywood.

Method used

The nanoparticles of magnesium hydroxide modified by tannin acid react with hyperbranched polymer and surface modified by Schiff base to form an organic-inorganic hybrid flame retardant adhesive, which improves the bonding strength and flame retardant properties through covalent crosslinking, and improves the dispersion of magnesium hydroxide through core-shell structure.

Benefits of technology

Adhesives with high strength, water resistance and good flame retardant properties are suitable for wood bonding and plywood, meeting the safety needs of the construction and furniture industry and reducing environmental and health impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248822A_ABST
    Figure CN120248822A_ABST
Patent Text Reader

Abstract

The invention discloses a tannic acid-based organic-inorganic hybrid flame-retardant adhesive and a preparation method thereof, the adhesive is composed of oxidized tannic acid (OTA), a hyperbranched polymer (HPA) and magnesium hydroxide nanoparticles (Mg (OH) 2-NH2) with amino groups modified on the surface, and the adhesive is formed by covalent crosslinking through Schiff base reaction. The adhesive disclosed by the invention has super-strong bonding strength, water resistance and good flame retardant property. The interfacial compatibility between the Mg (OH) 2-NH2 nano material and the adhesive is enhanced through the intermediary effect of the HPA, and the uniform dispersion of the adhesive is promoted. Through hot-pressing curing, the adhesive has excellent bonding performance and flame retardant performance. This combination results in a wood adhesive strength of 1.52 MPa, a limit oxygen index of 79%, and an excellent cone calorimetric test result. The raw materials used in the invention are safe and environment-friendly, and the adhesive has super-strong bonding strength, water resistance and good flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials science and engineering applications, and particularly relates to an organic-inorganic hybrid flame retardant adhesive based on tannic acid and a preparation method thereof. Background Art

[0002] With the continuous enhancement of global environmental protection awareness, developing renewable resources to replace traditional petrochemical raw materials has become one of the important directions of scientific research. Among them, tannic acid, as a natural polyphenol compound derived from agricultural and forestry wastes, has attracted much attention due to its unique chemical properties and abundant functional groups. Tannic acid is not only widely used in industries such as cosmetics, medicine, and leather tanning, but also shows great potential in the development of high-performance bio-based adhesives in recent years.

[0003] Adhesives play an important role in manufacturing industries such as construction, household, shipbuilding, and electronic products. However, traditional adhesives such as urea-formaldehyde resin, phenolic resin, and melamine-formaldehyde resin have the problem of formaldehyde release, and formaldehyde is considered a proven carcinogen, posing a serious threat to human health and environmental safety. Therefore, there is an urgent need to develop alternative and safe formaldehyde-free adhesives. Bio-based adhesives have become excellent candidates due to their environmental friendliness, and some biomass formaldehyde-free adhesives have been industrialized, which has greatly stimulated people's research interest. In the field of adhesive research, biomass resources include pyranose ring structure types (glucose, starch, cellulose, and chitosan), polyphenols (lignin, mussel, and tannic acid), and proteins. Although these materials can be used directly, it is often difficult to achieve ideal performance indicators. Inspired by mussel foot protein, mimicking its underwater adhesion strategy has become the key to developing water-resistant bio-based adhesives. However, due to the high price of dopamine, it is difficult to achieve large-scale industrial production. Interestingly, plant tannic acid (TA), as a natural polyphenol, not only has a catechol structure similar to that of mussels but also exhibits similar homologous functions such as the high reactivity and chelating ability of phenolic hydroxyl groups. These properties enable tannic acid to self-crosslink by forming quinone groups under specific conditions and form covalent bonds with nucleophilic groups, enhancing the interfacial binding force. The structural characteristics of tannic acid endow it with excellent adhesive properties, good water resistance, and excellent thermal stability. These properties stem from the ability of its phenolic hydroxyl groups to be easily oxidized to form quinone groups under specific conditions, as well as the properties of quinone groups to undergo Schiff base reactions and Michael addition reactions with nucleophilic amino groups. These reactions not only promote the crosslinking between tannic acid molecules, forming a stable three-dimensional network structure, but also enhance the physical and chemical properties of the adhesive. In addition, the research and development of tannic acid adhesives have also been inspired by natural bioadhesives, such as the phenolic-amine synergistic chemical principle involved in the hardening process of insect exoskeletons. This bio-inspired method not only improves the comprehensive performance of the adhesive but also reduces the impact on the environment, conforming to the concept of sustainable development.

[0004] As a bio-based adhesive, tannic acid can not only meet the requirements of high-performance adhesives but also effectively utilize agricultural and forestry waste, reduce dependence on fossil fuels, and promote the development of a circular economy. This study aims to further explore the optimization scheme of tannic acid adhesives in order to promote their popularization and development in practical industrial applications.

[0005] To further improve the performance of adhesives, especially enhance their toughness, rigidity, and water resistance, hyperbranched polymers (HBP) are introduced into the system. Compared with traditional linear or dendritic polymers, hyperbranched polymers have a unique three-dimensional structure and a high degree of branching, which enables them to exhibit excellent solubility, low viscosity, and high reactivity at relatively low molecular weights. Notably, hyperbranched polysiloxane (HBPSiO) can effectively improve the toughness of thermosetting resins due to its soft Si-O bond segments, making it an ideal toughening modifier. The addition of hyperbranched polymers not only increases the flexibility of adhesives but also promotes the formation of a denser crosslinked network within the adhesives through their abundant terminal functional groups and highly branched structure. This molecular-level network structure can effectively disperse and absorb external forces, thereby significantly enhancing the impact resistance and durability of adhesives. In addition, due to the relatively large intramolecular free volume of hyperbranched polymers, the entanglement between molecules is reduced, the viscosity of the adhesive is lowered, making it easier to coat and process. At the same time, the water resistance of the adhesive is improved, enabling it to maintain good bonding strength in humid environments.

[0006] After solving the water resistance problem of plywood, its flammability has become the next technical barrier that needs to be overcome urgently. Inspired by the fact that magnesium hydroxide can rapidly decompose under high-temperature conditions, release water, absorb a large amount of heat, and generate non-combustible gases at the same time, effectively curbing the spread of flames, it is proposed to fill magnesium hydroxide into the adhesive system. However, this direct filling method will inevitably weaken the mechanical properties of plywood to a certain extent because the addition of flame retardants may interfere with the continuity of the matrix material and reduce the overall strength. To solve this problem, a surface chemical modification technique is adopted, using APTES (3-aminopropyltriethoxysilane) to create a core-shell structure and tightly wrap magnesium hydroxide in it. This integrated method can not only effectively prevent the unexpected leakage of magnesium hydroxide particles but also significantly reduce its adverse effects on the properties of the polymer matrix, avoiding weakening the mechanical properties of plywood to a certain extent and ensuring the stability and safety of the material.

[0007] Currently, there is a lack of an organic-inorganic hybrid flame-retardant adhesive based on tannic acid and its preparation method. Summary of the Invention

[0008] The purpose of the present invention is to provide an organic-inorganic hybrid flame-retardant adhesive based on tannic acid and its preparation method.

[0009] To solve the problems of the existing technology, the present invention provides the following technical solutions: In the first aspect, the present application provides a preparation method of an organic-inorganic hybrid flame-retardant adhesive based on tannic acid.

[0010] Second aspect, the present application provides an organic-inorganic hybrid flame-retardant adhesive based on tannic acid.

[0011] Third aspect, the present application provides a method for bonding wood using an organic-inorganic hybrid flame-retardant adhesive based on tannic acid.

[0012] Fourth aspect, the present application provides a method for preparing a flame-retardant coating.

[0013] Fifth aspect, the present application provides a method for preparing a plywood with flame retardancy.

[0014] The method for preparing an organic-inorganic hybrid flame-retardant adhesive based on tannic acid provided in the first aspect of the present application includes the following steps: (1) Prepare oxidized tannic acid OTA, hyperbranched polymer HPA, and amino-modified magnesium hydroxide nanoparticles Mg(OH) 2- NH2;

[0015] (2) Mix oxidized tannic acid OTA and hyperbranched polymer HPA at a molar ratio of 1:1;

[0016] (3) Add the mass fraction of amino-modified magnesium hydroxide nanoparticles Mg(OH)2-NH2 to be 1-10%;

[0017] (4) Covalently crosslink the added components through Schiff base reaction to obtain an organic-inorganic hybrid flame-retardant adhesive based on tannic acid.

[0018] Further, in step (1), to prepare hyperbranched polymer HPA: Take 0.1-0.5 moles of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 moles of triethanolamine TEA, and 0.1% of p-toluenesulfonic acid p-TSA, place them in a 250 mL three-necked flask with a distillation device, heat to 120 °C under a nitrogen atmosphere, and maintain this temperature until the by-product ethanol is distilled off, then maintain the temperature of the system at 180 °C until no more distillation by-products are produced.

[0019] Further, in step (1), to prepare magnesium hydroxide nanoparticles Mg(OH)2-NPs: Prepare by co-precipitation method: Drop 1M NaOH aqueous solution into 1M MgCl2-6H2O aqueous solution, and place it in a 500 mL glass beaker, while slowly stirring for 10 minutes. The obtained mixture is left to stand for 3 hours at room temperature RT to precipitate. After centrifugation with a relative centrifugal force RCF of 300g for 5 minutes, collect the precipitate, wash it 4 times with deionized water, and wash it 2 times with 99.9% ethanol EtOH. Initially, the prepared Mg(OH)2-NPs are dried in a vacuum at 60 °C to obtain grafted clay Mg(OH)2-NPs.

[0020] Further, in step (1), prepare amino-modified magnesium hydroxide nanoparticles Mg(OH)₂-NH₂: Disperse 0.4 g of NPs in 60 mL of deionized water / ethanol solution, where the volume ratio of deionized water to ethanol in the deionized water / ethanol solution is 1:1; use it at 40 °C with constant stirring; when the temperature rises to 50 °C, add 1.2 mL of tetraethoxysilane TEOS dropwise, and after 6 hours, as a precursor for the silylation reaction, add 1.2 mL of ammonia water NH₄OH₂; keep the mixture under constant stirring for 6 hours, and wash the NPs with ethanol multiple times with a relative centrifugal force RCF of 300 g to eliminate possible reaction excess; disperse the NPs in 60 mL of N,N-dimethylformamide DMF, stir at 60 °C and 200 g, and during this process, add 1.2 mL of 3-aminopropyltriethoxysilane APTES dropwise, and keep it under constant stirring for 6 hours; wash the NPs with ethanol multiple times at 300 g for 5 minutes each time to obtain grafted clay, and the prepared sample is designated as Mg(OH)₂-NH₂.

[0021] Further, in step (1), prepare oxidized tannic acid OTA: Dissolve 5 g of tannic acid TA in deionized water and stir at 80 °C in a water bath for 5 minutes until all the tannic acid is dissolved; induce the oxidation of phenolic hydroxyl groups to quinone groups by adding 0.5 g of hydrogen peroxide H₂O₂ solution to form oxidized tannic acid OTA, and adjust the pH value of the mixture to 7.0 using 0.1 mol / L sodium hydroxide NaOH solution; freeze-dry the obtained oxidized tannic acid solution.

[0022] An organic-inorganic hybrid flame retardant adhesive based on tannic acid prepared by the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid provided in the second aspect of the present invention.

[0023] A wood bonding method using an organic-inorganic hybrid flame retardant adhesive based on tannic acid provided in the third aspect of the present invention, comprising the following steps: Apply the adhesive to the wood surface, hot press at 100 °C - 180 °C for 240 - 600 seconds, and then place it at room temperature for 24 hours to eliminate internal stress.

[0024] A preparation method of a flame retardant coating provided in the fourth aspect of the present invention, comprising the following steps: Dissolve ammonium polyphosphate in water, and then brush it on the surface of a plywood bonded with an organic-inorganic hybrid flame retardant adhesive based on tannic acid.

[0025] A preparation method of a plywood with flame retardancy provided in the fifth aspect of the present invention, comprising the following steps: Use the bonding method.

[0026] Beneficial effects: The raw materials used in the present invention are green, non-toxic, formaldehyde-free, safe and environmentally friendly. The adhesive has super strong bonding strength, water resistance and good flame retardant performance.

[0027] Compared with the prior art, the present invention has the following advantages: (1) Super strong bonding strength of the present invention: Through covalent cross-linking mediated by Schiff base chemistry, Mg(OH)2-NH2 combines with OTA to form a microphase separation structure similar to the exoskeleton of marine arthropods. This combination produces a wood bonding strength of 1.52 MPa.

[0028] (2) Excellent flame retardant performance: The plywood prepared with the organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention has a limiting oxygen index of 79%, and excellent cone calorimeter test results, showing good flame retardant performance. Water resistance: After the adhesive of the present invention is soaked in hot water at 63°C for 3 hours, the bonding strength of the plywood can still reach 1.34 MPa. Even when soaked in boiling water for 3 hours, the bonding strength only slightly decreases to 1.06 MPa, showing excellent water resistance.

[0029] (3) Enhanced interfacial compatibility: The interfacial compatibility between Mg(OH)2-NH2 nanomaterials and the adhesive is enhanced through the mediation of HPA, promoting the uniform dispersion of the adhesive. Simple preparation method: The preparation method of the organic-inorganic hybrid flame retardant adhesive of the present invention is simple and low in cost.

[0030] (4) Improve the safety of the wood industry: Through innovative flame retardant technology, the safety of plywood is improved, meeting the needs of the construction and furniture industries. Reduce environmental and health impacts: By improving the formula and process, the performance of the adhesive is improved, reducing the impact on the environment and human health.

[0031] (5) Wide application prospects: The bio-mimetic flame retardant adhesive of the present invention has wide application prospects in the wood industry, and can provide an environmentally friendly and efficient bonding solution. Description of the drawings

[0032] The drawings forming a part of this application are used to provide a further understanding of this application. The schematic embodiments and descriptions thereof of this application are used to explain this application and do not constitute an improper limitation of this application. In the drawings:

[0033] Figure 1 It is a reaction process and mechanism diagram of the HPA / OTA / Mg(OH)2-NH2 nanocomposite of the adhesive of the present invention.

[0034] Figure 2 It is a schematic diagram of the cross-linking network principle of the adhesive reaction of the present invention. Detailed implementation manners

[0036] In order to make the technical problems to be solved, technical solutions and beneficial effects of this application clearer and more understandable, the following further elaborates on this application in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit this application.

[0037] In this application, the term "and / or" describes the association relationship of associated objects and indicates that three relationships can exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. Where A and B can be singular or plural. The character " / " generally represents an "or" relationship between the associated objects before and after.

[0038] In this application, "at least one" means one or more, and "a plurality" means two or more. "At least one of the following items" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or, "at least one of a, b, and c" can both represent: a, b, c, a - b (that is, a and b), a - c, b - c, or a - b - c, where a, b, and c can be single or multiple respectively.

[0039] It should be understood that in various embodiments of this application, the magnitudes of the serial numbers of the above processes do not mean the order of execution. Some or all steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation to the implementation process of the embodiments of this application.

[0040] The terms used in the embodiments of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms "a", "the", and "said" used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0041] The weights of the relevant components mentioned in the specification of the embodiments of this application can not only refer to the specific contents of each component, but also represent the proportional relationship of the weights between the components. Therefore, as long as the contents of the relevant components in the specification of the embodiments of this application are scaled up or down in proportion, they are within the scope disclosed in the specification of the embodiments of this application. Specifically, the mass described in the specification of the embodiments of this application can be mass units well-known in the chemical industry such as μg, mg, g, kg, etc.

[0042] The terms "first" and "second" are for descriptive purposes only, used to distinguish objects such as substances from each other, and should not be construed as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined with "first" and "second" may explicitly or implicitly include one or more of such features.

[0043] The first aspect of the embodiments of the present application provides a preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid, including the following steps: The organic-inorganic hybrid flame retardant adhesive is composed of oxidized tannic acid OTA, hyperbranched polymer HPA, and amino-modified magnesium hydroxide nanoparticles Mg(OH)2-NH2 with surface-modified amino groups. Add oxidized tannic acid, hyperbranched polymer HPA, and surface-modified amino-modified magnesium hydroxide nanoparticles respectively, and through Schiff base reaction and covalent cross-linking reaction, an organic-inorganic hybrid flame retardant adhesive is prepared. Oxidized tannic acid (OTA): It is a natural polysaccharide with good biocompatibility and biodegradability. It can be obtained from tannic acid by chemical or physical methods and has enhanced hydrophilicity and reactivity. Hyperbranched polymer (HPA): It has a highly branched structure, which can provide multiple reaction sites, increasing the cross-linking density and mechanical strength of the adhesive. Surface-modified amino-modified magnesium hydroxide nanoparticles (Mg(OH)2-NH2): Vermiculite is a layered silicate mineral. After surface modification, its compatibility with organic polymers can be improved, enhancing the flame retardant performance of the adhesive.

[0044] In some embodiments, a preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention includes the following steps: (1) Prepare oxidized tannic acid OTA, hyperbranched polymer HPA, and amino-modified magnesium hydroxide nanoparticles Mg(OH)2-NH2 respectively;

[0045] (2) Mix oxidized tannic acid OTA and hyperbranched polymer HPA in a molar ratio of 1:1; Mix oxidized tannic acid OTA and hyperbranched polymer HPA in a molar ratio of 1:1. This ratio can adjust the viscosity and mechanical properties of the adhesive to meet different application requirements;

[0046] (3) The mass fraction of added amino-modified magnesium hydroxide nanoparticles Mg(OH)2-NH2 is 1-10%; This ratio can ensure that the adhesive has good flame retardant performance without significantly affecting its bonding performance;

[0047] (4) The added components are covalently crosslinked through the Schiff base reaction to prepare an organic-inorganic hybrid flame retardant adhesive. Covalent crosslinking is carried out through the Schiff base reaction; the Schiff base reaction is an effective covalent crosslinking method, which can form stable chemical bonds between oxidized tannic acid OTA, hyperbranched polymer HPA, and amino-modified magnesium hydroxide nanoparticles Mg(OH)2-NH2, enhancing the stability and durability of the adhesive, and preparing an organic-inorganic hybrid flame retardant adhesive based on tannic acid.

[0048] In some embodiments, in step (1), to prepare the hyperbranched polymer HPA: 0.1 - 0.5 moles of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 moles of triethanolamine TEA, and 0.1% p-toluenesulfonic acid (p-TSA) are placed in a 250 mL three-necked flask equipped with a distillation device, heated to 120 °C under a nitrogen atmosphere, and maintained at this temperature until the by-product ethanol is distilled off. Then the temperature of the system is maintained at 180 °C until no more distillation by-products are produced.

[0049] In some embodiments, in step (1), to prepare the magnesium hydroxide nanoparticles Mg(OH)2-NPs: They are prepared by the co-precipitation method. A 1M NaOH aqueous solution is dropped into a 1M MgCl2-6H2O aqueous solution in a glass beaker (500 mL), while gently stirring for 10 minutes. The resulting mixture is allowed to stand at room temperature (RT) for 3 hours to precipitate. The precipitate is collected by centrifugation (300 g, 5 minutes) and washed four times with deionized water and twice with 99.9% ethanol (EtOH). Initially, the prepared Mg(OH)2-NPs are dried in vacuo at 60 °C. The grafted clay is designated as Mg(OH)2-NPs.

[0050] In some embodiments, in step (1), the preparation of amino-modified magnesium hydroxide nanoparticles Mg(OH)₂-NH₂: 0.4 g of NPs is dispersed in 60 mL of deionized water / ethanol (1:1) solution and used under constant stirring at 40 °C. Further, when the temperature is raised to 50 °C, 1.2 mL of tetraethoxysilane (TEOS) is added dropwise. After 6 hours, as a precursor for the silanization reaction, 1.2 mL of ammonia water (NH₄OH₂) is added. The mixture is kept under constant stirring for 6 hours. The NPs are washed several times with ethanol by centrifugation (300 g) to eliminate possible reaction excess. Then, the NPs are dispersed in 60 mL of N,N-dimethylformamide (DMF), and 1.2 mL of 3-aminopropyltriethoxysilane (APTES) is added dropwise during this process under stirring at 60 °C and 200 g, and kept under constant stirring for 6 hours. Finally, the NPs are washed several times with ethanol at 300 g for 5 minutes each time. The grafted clay thus prepared is designated as Mg(OH)₂-NH₂.

[0051] In some embodiments, in step (1), the preparation of oxidized tannic acid OTA: 5 g of tannic acid (TA) is dissolved in deionized water and stirred in a water bath at 80 °C for 5 minutes. Until all the tannic acid is dissolved, then, by adding 0.5 g of hydrogen peroxide (H₂O₂) solution, the phenolic hydroxyl groups are induced to oxidize into quinone groups to form oxidized tannic acid (OTA), and the pH value of the mixture is adjusted to 7.0 using 0.1 mol / L sodium hydroxide (NaOH) solution. Then the obtained oxidized tannic acid solution is freeze-dried.

[0052] In the second aspect of the embodiments of the present application, an organic-inorganic hybrid flame-retardant adhesive is prepared by a preparation method of an organic-inorganic hybrid flame-retardant adhesive based on tannic acid.

[0053] In the third aspect of the embodiments of the present application, a wood bonding method of an organic-inorganic hybrid flame-retardant adhesive based on tannic acid includes the following steps: applying the adhesive to the wood surface, hot pressing at 100 °C - 180 °C for 240 - 600 seconds, and then placing it at room temperature for 24 hours to eliminate internal stress. Post-treatment: This step helps to improve the long-term stability of the adhesive and reduce cracks that may occur during the wood bonding process.

[0054] In the fourth aspect of the embodiments of the present application, a preparation method of a plywood with flame retardancy is provided, using the bonding method and flame-retardant coating.

[0055] In the fifth aspect of the embodiments of the present application, a preparation method of a flame-retardant coating includes the following steps: dissolving ammonium polyphosphate in water, and then brushing it on the surface of the plywood.

[0056] Example 1

[0057] A preparation method of an organic-inorganic hybrid flame-retardant adhesive of the present invention comprises the following steps:

[0058] (1) Preparation of HPA: Take 0.4 mol of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 mol of triethanolamine TEA, and 0.1% of p-toluenesulfonic acid (p-TSA), and place them in a 250 mL three-necked flask equipped with a distillation device. Heat it to 120 °C under a nitrogen atmosphere and maintain this temperature until the by-product ethanol is distilled off. Then maintain the temperature of the system at 180 °C until no more distillation by-products are produced.

[0059] Preparation of magnesium hydroxide nanoparticles Mg(OH)2-NPs: It is prepared by the co-precipitation method. Briefly, a 1M NaOH aqueous solution is dropped into a 1M MgCl2·6H2O aqueous solution in a glass beaker (500 mL), while gently stirring for 10 minutes. The resulting mixture is allowed to stand at room temperature (RT) for 3 hours to precipitate. The precipitate is collected by centrifugation (300 g, 5 minutes) and washed four times with deionized water and twice with 99.9% ethanol (EtOH). Initially, the prepared Mg(OH)2-NPs are dried in vacuo at 60 °C. The grafted clay thus obtained is designated as Mg(OH)2-NPs.

[0060] Preparation of amino-modified magnesium hydroxide nanoparticles Mg(OH)2-NH2: Use 0.4 g of NPs dispersed in a 60 mL deionized water / ethanol (1:1) solution and use it under constant stirring at 40 °C. Further, when the temperature is raised to 50 °C, 1.2 mL of tetraethoxysilane (TEOS) is added dropwise. After 6 hours, as a precursor for the silylation reaction, 1.2 mL of ammonia water (NH4OH2) is added. The mixture is kept under constant stirring for 6 hours. The NPs are washed several times with ethanol by centrifugation (300 g) to remove possible reaction excess. Then, the NPs are dispersed in 60 mL of N,N-dimethylformamide (DMF), and 1.2 mL of 3-aminopropyltriethoxysilane (APTES) is added dropwise under stirring at 60 °C and 200 g, and the mixture is kept under constant stirring for 6 hours. Finally, the NPs are washed several times with ethanol at 300 g for 5 minutes each time. The grafted clay thus obtained is designated as Mg(OH)2-NH2.

[0061] Preparation of oxidized tannic acid OTA: Dissolve 5 grams of tannic acid (TA) in deionized water and stir for 5 minutes in a water bath at 80 °C until all the tannic acid is dissolved. Then, induce the oxidation of phenolic hydroxyl groups to quinone groups by adding 0.5 grams of hydrogen peroxide (H2O2) solution to form oxidized tannic acid (OTA), and adjust the pH value of the mixture to 7.0 using 0.1 molar / liter sodium hydroxide (NaOH) solution. Then freeze-dry the resulting oxidized tannic acid solution.

[0062] (2) Dissolve 4 g of OCTA in 4 g of water to obtain an OTA solution;

[0063] (3) Add 0.5 g of MG(OH)2-NH2 and 4 g of HPA to 8 grams of OTA aqueous solution and stir at room temperature for 30 minutes. Then gradually add hydrochloric acid until the pH value of the solution reaches 6, obtaining an organic-inorganic hybrid flame retardant adhesive based on tannic acid.

[0064] The usage method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention includes the following steps:

[0065] Coat the prepared above-mentioned organic-inorganic hybrid flame retardant adhesive on the plywood and hot-press at 160 °C for 360 s, and place the prepared plywood for 24 hours to eliminate internal stress.

[0066] Dissolve ammonium polyphosphate in water to form a transparent solution, and then brush it on the surface of the plywood.

[0067] Example 2

[0068] The difference between Example 2 and Example 1 is only that: The preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention includes the following steps: In step (1), for the preparation of HPA, take 0.1 mole of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 mole of triethanolamine TEA, and 0.1% of p-toluenesulfonic acid (p-TSA), put them into a 250 ml three-necked flask equipped with a distillation device, heat to 120 °C under a nitrogen atmosphere, and maintain this temperature until the by-product ethanol is distilled off. Then maintain the temperature of the system at 180 °C until no more distillation by-products are produced.

[0069] The hot-pressing temperature is 120 °C, and the remaining process steps and parameters are the same as those in Example 1.

[0070] Example 3

[0071] Example 3 is only different from Example 1 in that: in the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention, the following steps are included: in step (1), for the preparation of HPA, 0.5 moles of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 moles of triethanolamine TEA, and 0.1% of p-toluenesulfonic acid (p-TSA) are placed in a 250 ml three-necked flask equipped with a distillation device, heated to 120 °C under a nitrogen atmosphere, and maintained at this temperature until the by-product ethanol is distilled off. Then the temperature of the system is maintained at 180 °C until no more distillation by-products are produced. The hot pressing temperature is 140 °C, and the remaining process steps and parameters are the same as those in Example 1.

[0072] Example 4

[0073] Example 4 is only different from Example 1 in that: in the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention, in step (1), the hot pressing temperature is 180 °C, and the remaining process steps and parameters are the same as those in Example 1.

[0074] Example 5

[0075] Example 6 is only different from Example 1 in that: in the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention, in step (1), the hot pressing time is 240 s, and the remaining process steps and parameters are the same as those in Example 1.

[0076] Example 6

[0077] Example 7 is only different from Example 1 in that: in the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention, in step (1), the hot pressing time is 480 s, and the remaining process steps and parameters are the same as those in Example 1.

[0078] Example 7

[0079] Example 8 is only different from Example 1 in that: in the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention, in step (1), the hot pressing time is 600 s, and the remaining process steps and parameters are the same as those in Example 1.

[0080] Comparative Example 1

[0081] Comparative Example 1 is only different from Example 1 in that: in the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention, in step (1), HPA is not added, and the remaining process steps and parameters are the same as those in Example 1.

[0082] Comparative Example 2

[0083] The difference between Comparative Example 2 and Example 1 is only that: in the preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid of the present invention, in step (1), Mg(OH)2-NH2 is not added, and the remaining process steps and parameters are the same as those in Example 1.

[0084] The physical and mechanical properties of the above materials were tested using a universal mechanical testing machine. The bonding strength of the plywood was tested with reference to the GB / T 17657-2022 standard, and the results of the bonding strength are shown in Table 1.

[0085] Table 1

[0086] Plywood specimen Gluing strength (MPa) Example 1 1.52 Example 2 0.9 Example 3 1.1 Example 4 1.47 Example 5 0.5 Example 6 1.52 Example 7 1.52 Comparative example 1 0.2 Comparative example 2 1.34

[0087] From the bonding strength data in Table 1 of Comparative Example 21.4, it can be seen that the bonding performance of the plywood prepared from OTA / HPA / Mg(OH)2-NH2 is much higher than that of the plywood prepared from OTA / Mg(OH)2-NH2 and OTA / HPA, which also shows that after adding the HPA solution, the bonding performance of the prepared plywood can be further improved.

[0088] With reference to the ISO 4589-2 limiting oxygen index test standard, the flame retardant performance of the plywood was tested, and the results of the limiting oxygen index are shown in Table 2.

[0089] Table 2

[0090]

[0091] Figure 1 It is a reaction process and mechanism diagram of the HPA / OTA / Mg(OH)2-NH2 nanocomposite of the adhesive of the present invention;

[0092] Figure 2 It is a schematic diagram of the crosslinking network principle of the reaction of the adhesive of the present invention. Through careful X-ray photoelectron spectroscopy (XPS) analysis, we have confirmed the chemical composition and elemental state on the surface of the product, such as Figure 2. During the detailed examination of the chemical composition and elemental state of the product surface, a decrease in the intensity of the C=O peak was observed when comparing the C1s peaks of OTA (compound) and OTA / Mg(OH)2-NH2 composite, accompanied by a significant appearance of the C=N peak, a shift that directly indicates the occurrence of a Schiff base reaction between the quinone group (-C=O) and the amino group (-NH2). Similarly, the weakening of the intensity of the C=O peak when comparing the O1s spectra of OTA and OTA / Mg(OH)2-NH2 further validates the above chemical reaction process. These XPS analysis results are in full agreement with the reaction mechanism revealed by the infrared spectroscopy (FT-IR) data, further strengthening the conclusion that the reaction between OTA and amino-modified Mg(OH)2 is feasible. Further comparison of the C1s signal of the HPA / OTA system also observed a decrease in the C=O peak and the generation of the C=N peak, and the C=O peak was also weakened in the corresponding O1s spectrum, indicating that the amino group on HPA can also effectively react with the quinone group on OTA, which is consistent with the FT-IR analysis results, and once again verifies the universality of this type of chemical reaction pathway. More importantly, the changes in the C1s and O1s spectra of the HPA / OTA / Mg(OH)2-NH2 ternary system, namely the disappearance of the C=O peak and the generation of the C=N peak, not only directly prove that OTA can react effectively with Mg(OH)2-NH2 and HPA at the same time, but also indicate the successful synthesis of the HPA / OTA / Mg(OH)2-NH2 composite material. These XPS analysis results strongly prove the feasibility of using OTA as a crosslinker to achieve an effective crosslinking strategy between amino-functionalized inorganic nano-magnesium hydroxide (Mg(OH)2-NH2) and hyperbranched polymers (HPA). When Fourier transform infrared spectroscopy (FT-IR) was performed on the HPA (hyperbranched polymer) / OTA system, we observed a -1 This finding can be attributed to the C=N stretching vibration absorption formed by the Schiff base reaction between the quinone group in OTA and the amino group on HPA, which strongly proves the possibility of chemical reaction between OTA and HPA. Furthermore, when studying the interaction between OTA and magnesium hydroxide nanoparticles (Mg(OH)2-NH2), the infrared spectrum at 1664cm -1 A new peak shape was revealed at 1655 cm-1. This was also interpreted as the C=N vibration mode unique to the amino-inter-Schiff base reaction of the quinone group on OTA and Mg(OH)2-NH2, confirming that OTA and Mg(OH)2-NH2 can react effectively. More importantly, in the infrared spectrum analysis of the HPA / OTA / Mg(OH)2-NH2 ternary composite system, we found a peak at 1655 cm-1. -1The new peak position. This peak position is not only consistent with the C=N stretching vibration peak previously observed in the HPA / OTA and OTA / Mg(OH)2-NH2 systems, but also strongly indicates that OTA, as a cross-linking medium, can interact with the amino groups of both HPA and Mg(OH)2-NH2 simultaneously, thereby forming a complex network structure constructed by Schiff base cross-linking. The consistency of this series of infrared spectroscopy data not only provides direct evidence for the successful preparation of the HPA / OTA / Mg(OH)2-NH2 composite material, but also verifies the rationality and feasibility of the efficient cross-linking strategy of using OTA as a cross-linking agent to achieve the cross-linking of amino group-modified inorganic nano-magnesium hydroxide particles and hyperbranched polymer HPA at the molecular level.

[0093] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. What is described in the above embodiments and the specification only illustrates the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements. The scope of protection required by the present invention is defined by the appended claims, the specification and their equivalents.

Claims

1. A preparation method of an organic-inorganic hybrid flame retardant adhesive based on tannic acid, characterized in that It includes the following steps: (1) Prepare oxidized tannic acid OTA, hyperbranched polymer HPA, and amino-modified magnesium hydroxide nanoparticles Mg(OH)₂-NH₂ respectively; (2) Mix oxidized tannic acid OTA and hyperbranched polymer HPA at a molar ratio of 1:1; (3) The mass fraction of amino-modified magnesium hydroxide nanoparticles Mg(OH)₂-NH₂ added is 1-10%; (4) Add each component to a beaker, and covalently crosslink each component through Schiff base reaction to obtain a tannic acid-based organic-inorganic hybrid flame retardant adhesive.

2. The preparation method of the tannic acid-based organic-inorganic hybrid flame retardant adhesive according to claim 1, wherein: In step (1), to prepare hyperbranched polymer HPA: Take 0.1-0.5 moles of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 moles of triethanolamine TEA, and 0.1% of p-toluenesulfonic acid p-TSA, place them in a 250 mL three-necked flask equipped with a distillation device, heat to 120 °C under a nitrogen atmosphere, and maintain this temperature until the by-product ethanol is distilled off, then maintain the temperature of the system at 180 °C until no more distillation by-products are produced.

3. The preparation method of the tannic acid-based organic-inorganic hybrid flame retardant adhesive according to claim 1, characterized in that: In step (1), to prepare magnesium hydroxide nanoparticles Mg(OH)₂-NPs: Drop 1M NaOH aqueous solution into 1M MgCl₂·6H₂O aqueous solution, and place it in a 500 mL glass beaker, while slowly stirring for 10 minutes. Let the obtained mixture stand for 3 hours at room temperature RT to precipitate. After centrifugation with a relative centrifugal force RCF of 300g for 5 minutes, collect the precipitate, wash it 4 times with deionized water, and wash it 2 times with 99.9% ethanol EtOH. Initially, the prepared Mg(OH)₂-NPs are dried in a vacuum at 60 °C to obtain grafted clay Mg(OH)₂-NPs.

4. The preparation method of the tannic acid-based organic-inorganic hybrid flame retardant adhesive according to claim 1, characterized in that: In step (1), to prepare amino-modified magnesium hydroxide nanoparticles Mg(OH)₂-NH₂: Use 0.4 g of NPs dispersed in 60 mL of deionized water / ethanol solution, and the volume ratio of deionized water to ethanol in the deionized water / ethanol solution is 1:1; use it at 40 °C with constant stirring; when the temperature is raised to 50 °C, add 1.2 mL of tetraethoxysilane TEOS. After 6 hours, as a precursor for the silylation reaction, add 1.2 mL of ammonia water NH₄OH₂; keep the mixture under constant stirring for 6 hours. Wash the NPs with ethanol multiple times with a relative centrifugal force RCF of 300g to eliminate possible reaction excess; disperse the NPs in 60 mL of N,N-dimethylformamide DMF, stir at 60 °C and 200g, and during this process, add 1.2 mL of 3-aminopropyltriethoxysilane APTES, and keep it under constant stirring for 6 hours; wash the NPs with ethanol multiple times at 300g for 5 minutes each time to obtain grafted clay Mg(OH)₂-NH₂.

5. The preparation method of the tannic acid-based organic-inorganic hybrid flame retardant adhesive according to claim 1, characterized in that: In step (1), the preparation of oxidized tannic acid OTA: Dissolve 5 g of tannic acid TA in deionized water and stir for 5 minutes in a water bath at 80 °C until all the tannic acid is dissolved; induce the oxidation of phenolic hydroxyl groups to quinone groups by adding 0.5 g of hydrogen peroxide H2O2 solution to form oxidized tannic acid OTA, and adjust the pH value of the mixture to 7.0 using 0.1 mol / L sodium hydroxide NaOH solution; freeze-dry the obtained oxidized tannic acid solution.

6. The tannic acid-based organic-inorganic hybrid flame-retardant adhesive prepared by the method for preparing a tannic acid-based organic-inorganic hybrid flame-retardant adhesive according to claim 1.

7. A method for bonding wood using the tannic acid-based organic-inorganic hybrid flame retardant adhesive according to any one of claims 1 to 3, characterized in that It includes the following steps: Apply the adhesive to the wood surface, hot press at 100 °C - 180 °C for 240 - 600 seconds, and then place it at room temperature for 24 hours to eliminate internal stress.

8. A method for preparing a flame-retardant coating, characterized in that It includes the following steps: Dissolve ammonium polyphosphate in water, and then brush it on the surface of the plywood bonded with the tannic acid-based organic-inorganic hybrid flame-retardant adhesive.

9. A preparation method of a flame-retardant plywood, characterized in that It includes the following steps: Use the wood bonding method according to claim 7.